1982
DOI: 10.1002/pol.1982.180200107
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of concentrated polystyrene solutions in large‐amplitude oscillating shear fields

Abstract: SynopsisThe limits of linear viscoelastic behavior of polystyrene solutions have been investigated by subjecting them to large-amplitude oscillatory strains, yo. At strains less than one we find that the dynamic storage modulus G'(o,yo) and the dynamic loss modulus G"(o,yo) decrease quadratically with increasing strain. As a measure of the size of the linear viscoelastic region, we have determined the strain a t which the moduli have fallen 5% below their zero-strain values. This strain, ~N L , is found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(74 citation statements)
references
References 28 publications
1
73
0
Order By: Relevance
“…Because of the quasi linear nature of the UCM model, the oscillatory first normal stress difference can be uniquely divided into three terms, given by Eq. (20). On the contrary, the simulation results of Giesekus model (Fig.…”
Section: Nonlinear Normal Stress Differencementioning
confidence: 89%
See 2 more Smart Citations
“…Because of the quasi linear nature of the UCM model, the oscillatory first normal stress difference can be uniquely divided into three terms, given by Eq. (20). On the contrary, the simulation results of Giesekus model (Fig.…”
Section: Nonlinear Normal Stress Differencementioning
confidence: 89%
“…Experiments were limited by the dynamic range of the torque transducer in the rheometers commonly used at this time, nonetheless, various analysis methods were already suggested at this early stage, especially stress shape analysis and Fourier transform analysis. Pearson and Rocherfort [20] and Helfand and Pearson [21] calculated nonlinear parameters under LAOS utilizing the Doi-Edwards model for polymer dynamics. They investigated the limits of linear viscoelastic behavior of concentrated polystyrene solutions.…”
Section: Historical Survey Of Laosmentioning
confidence: 99%
See 1 more Smart Citation
“…This full set of self-consistent equations is clearly very di cult to solve even numerically, and few serious studies have attempted this level of treatment, but they have been shown to perform better in large amplitude oscillatory¯ows than the IAA [321,322]. A di culty is that, even at this level, chain stretch (de®ned as a¯ow-induced increase in the primitive path length) is not taken into account.…”
Section: Double Step Strainsmentioning
confidence: 99%
“…As an explanation for these phenomena, attributed both shear banding and non-quiescent relaxation to "elastic yielding", which is a microscopic failure occurring in the bulk of the material under a large and abrupt strain. If such findings are universally valid, not only would the reptation models become unsupported by rheometric measurements, but also a significant amount of nonlinear rheology in polymer melts and solutions [Zapas and Craft (1965); Osaki et al (1981Osaki et al ( , 1993Osaki et al ( , 2000; Pearson and Rochefort (1982); Venerus and Kahvand (1994); Reimers and Dealy (1996); Hyun et al (1999); Sui and McKenna (2007)] would need to be reevaluated. Hence, the purpose of the present collaborative research has been to assess the validity of the results reported by Wang and co-workers.…”
Section: Introductionmentioning
confidence: 99%